Advertisement Remove all ads

Advertisement Remove all ads

Advertisement Remove all ads

Sum

**Solve the following differential equation:**

`2"e"^("x + 2y") "dx" - 3"dy" = 0`

Advertisement Remove all ads

#### Solution

`2"e"^("x + 2y") "dx" - 3"dy" = 0`

∴ `2"e"^"x" * "e"^"2y" "dx" - 3"dy" = 0`

∴ `2"e"^"x" "dx" - 3/"e"^"2y" "dy" = 0`

Integrating both sides, we get

`2 int "e"^"x" "dx" - 3 int "e"^(-2"y") "dy" = "c"_1`

∴ `2"e"^"x" - 3 * ("e"^(- "2y"))/(- 2) = "c"_1`

∴ `4"e"^"x" + 3"e"^(- 2"y") = 2"c"_1`

∴ `4"e"^"x" + 3"e"^(- 2"y") = "c"`, where c = 2c_{1}.

This is the general solution.

Concept: Formation of Differential Equations

Is there an error in this question or solution?

Advertisement Remove all ads

#### APPEARS IN

Advertisement Remove all ads